Serum Vitamin D Levels Related to Cognitive Function in Chronic Kidney Disease Patients - Elsi Rahmadhani Hardi; Yuliarni Syafrita; Syarif Indra (HM Publisher, 2022)
Background: Vitamin D acts as a neuroprotector and modulator in the central nervous system. Hypovitaminosis is a risk factor for cognitive dysfunction. Hypovitaminosis D and impaired cognitive function are common in patients with chronic kidney disease. Impaired cognitive function is comorbid that can increase the morbidity and mortality of patients with chronic kidney disease. This study aims to assess the relationship between serum vitamin D levels and cognitive function in patients with chronic kidney disease. Methods: This research is an observational study with a cross-sectional approach. A total of 60 research subjects participated in this study. Sociodemographic data, cognitive function, and vitamin D levels were analyzed in this study. Data analysis was performed with SPSS 25 to perform univariate and bivariate tests. Results: The impaired cognitive function was found in 56.7% of CKD patients. The median serum vitamin D level of patients with chronic kidney disease with impaired cognitive function was 30.80 ng/mL and without impaired cognitive function 42.98 ng/mL. There was a significant relationship between serum vitamin D levels and impaired cognitive function (OR=4.125, p=0.035). The cut-off point of serum vitamin D levels associated with impaired cognitive function in CKD patients was 34.8 ng/mL (sensitivity 64.7% and specificity 69.2%). Conclusion:There is a significant relationship between serum vitamin D levels and the incidence of cognitive dysfunction in patients with chronic kidney disease. The cut-off point for serum vitamin D levels associated with impaired cognitive function in chronic kidney disease is 34.8 ng/mL.